Style Shifting and Its Functions Beta Squad YouTube Channel - Pipit Anggita Wulandari; Elsan Arvian (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines style shifting and its communicative functions in the Last to Leave the Island video uploaded on the Beta Squad YouTube channel. It aims to identify the types of style shifting used by group members and analyze the underlying communicative functions of these linguistic variations during interaction. The study is grounded in sociolinguistic theories of style variation, including Labov’s (1972) Attention to Speech Theory, Bell’s (2014) Audience Design Theory, and Eckert and Rickford’s (2001) view of style as a resource for constructing social meaning and identity. A qualitative descriptive method was employed, with data collected through observation and documentation. The video was repeatedly viewed, transcribed, and analyzed using qualitative content analysis to identify utterances containing style shifting. The findings show that style shifting occurs frequently among Beta Squad members, including shifts from formal to casual, casual to competitive, serious to humorous, neutral to expressive, and cooperative variations. In addition, style shifting serves multiple communicative functions such as humour, audience engagement, solidarity building, emotional expression, instruction giving, cooperation, self-motivation, and identity construction. A total of 191 instances were identified, with humour as the most dominant function (31.4%), followed by solidarity (12.5%) and emotional expression (8.9%). Overall, style shifting functions as a strategic communicative resource in digital interaction, used to entertain audiences, strengthen relationships, and maintain effective communication in online media contexts.